Prognostic Factors in Lung Transplantation After Hematopoietic Stem Cell Transplantation. Issue 1 (January 2018) - Chen-Yoshikawa, Toyofumi F.; Sugimoto, Seiichiro; Shiraishi, Takeshi; Minami, Masato; Matsuda, Yasushi; Chida, Masayuki; Maeda, Sumiko; Aoyama, Akihiro; Okada, Yoshinori; Okumura, Meinoshin; Iwasaki, Akinori; Miyoshi, Shinichiro; et al.
Abstract : Background: Lung transplantation is the final lifesaving option for patients with pulmonary complications after hematopoietic stem cell transplantation (HSCT). Patients undergoing HSCT for hematologic diseases are thought to be high-risk candidates for lung transplantation; therefore, few lung transplants are performed for these patients, and few studies have been reported. This study aimed to describe the characteristics and outcomes of lung transplantation in patients with pulmonary complications after HSCT. Methods: We retrospectively investigated 62 patients who underwent lung transplantation after HSCT. All data were collected from 6 lung transplant centers in Japan. Results: Seventeen patients underwent cadaveric lung transplantation, whereas 45 underwent living-donor lobar lung transplantation (LDLLT). In the LDLLT group, 18 patients underwent LDLLT after HSCT in which one of the donors had also served as a donor for HSCT. Seven patients underwent single LDLLT for which the donor was the same as the patient from whom stem cells were obtained for HSCT. Preoperative hypercapnia was observed in 52 patients (84%). Thirteen patients (21%) required mechanical ventilation preoperatively. Fifty-five patients underwent HSCT for hematologic malignancies, and 4 (7%) relapsed after lung transplantation. The 5-year survival rate was 64.2%. In a multivariable analysis, patients younger than 45 years and those with the same donor for both procedures exhibited significantly better survival ( P = 0.012 and 0.041, respectively). Conclusions: Lung transplantation for pulmonary complications after HSCT was performed safely and yielded better survival, especially in younger recipients for whom both lung transplantation and HSCT involved the same donor. Abstract : This report describes living and deceased lung transplantation after prior hematopoietic stem cell transplant in a large cohort of patients. Better results are achieved with younger recipients and when the donor was the living donor who had previously been the stem cell donor.